A systems-theoretical look at stakeholder theory: Lessons from Bogdanov's Tektology - Vladislav Valentinov (Business and Society Review, 2025)
We explore how the conversation between stakeholder theory and systems theory can illustrate the unique role of stakeholder management within the system of capitalistic institutions. Toward that end, we call the attention of stakeholder scholars to Alexander Bogdanov's Tektology , an early version of systems theory that raised critical concerns about capitalism. According to Tektology, capitalism fosters individualistic and conflict-driven mindsets, which stymie society's ability to achieve its full collaborative potential. If stakeholder theory takes this critique on board, it may conceptualize social collaboration as “organized complexity” that can materialize if human actors overcome their reductionist mindsets. This conceptual move highlights novel systems-theoretical foundations for stakeholder theory's insights into the role of stakeholder mindsets in unlocking collaborative potential within capitalist societies. The resulting added value for stakeholder theory lies in recognizing the collaborative nature of capitalism as an institutional accomplishment facilitated by stakeholder management practices, which operate along non-linear pathways and generate emergent and counter-intuitive outcomes.
Keywords: 330; stakeholder theory; systems theory; Tektology